Co-ordination analysis of landing strategies in beam dismounts - Irwin, G.; Kerwin, D. G.; Robins, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: Landing strategies selected by female gymnasts performing somersault dismounts from the beam may be related to the availability of feedback (McNitt-Gray et al., 2001). This study aims to employ co-ordination analysis to examine how female gymnasts control dropping and landing from forward and backward somersault beam dismounts. METHOD: A female regional level gymnast performed 10 forward and 10 backward somersault dismounts from a competitive beam. Kinematic data for each skill were recorded at 200 Hz using a CODA (CX1) automated motion analysis system. CRP profiles of hip-knee and ankle-knee joint couplings and coefficients of variation were determined. RESULTS: Phase differences for each dismount in the drop and balance phases are shown in hip-knee coupling in both phases of backward dismounts were twice that of the forward dismounts. Forward somersaulting variability was similar in the knee-ankle coupling for forward and backward dismounts.